ESTIMASI SUMBERDAYA NIKEL LATERIT PADA BLOK 1A PT. XYZ PULAU GEBE - Supriyono; Jance Murdjani Supit (INTAN Jurnal Penelitian Tambang, 2020)
XYZ is a company engaged in the field of lateritic nickel mining, where the Mining Business License Area (WIUP) is located in Umera Village, Gebe Island District, Central Halmahera Regency, North Maluku Province. This study aims to estimate Block 1A lateritic nickel resources, and classify the lateritic nickel resources. The analysis conducted is univariate statistical analysis, outliers, semivariogram analysis, variogram validation, ordinary kriging estimation with the results obtained by tonnage of lateritic nickel resources (Ni) and kriging variance values ​​that can be used for determining the classification of resources through Relative Kriging Standard Deviation (RKSD). Indicated mineral resources of lateritic nickel in Block 1A is 3,240,730,596 tons.